2023
DOI: 10.1002/cbin.12025
|View full text |Cite
|
Sign up to set email alerts
|

PLAU contributes to the development of cholangiocarcinoma via activating NF‐κB signaling pathway

Abstract: Cholangiocarcinoma (CCA) is a type of epithelial cancer with poor outcomes and late diagnosis. Accumulating evidence has demonstrated the promoting role of plasminogen activator, urokinase (PLAU) in several tumor types, while its function in CCA is largely unknown. The expression of PLAU in CCA was determined by data from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) database and further confirmed in human tissues using immunohistochemical (IHC) staining. Moreover, PLAU‐silencing CCA cell mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…RLRs can collect specific intracellular junction proteins to initiate and activate signaling pathways such as NF-κB to control the transcription of genes encoding IFN-I and other inflammatory cytokines to inhibit virus replication ( 28 ). A previous study found that human PLAU could activate the NF-κB signaling pathway and participate in the development of bile duct cancer ( 20 ). We found high homology between human and goat PLAU using sequence alignment and investigated whether goat PLAU was involved in RLR-mediated signaling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RLRs can collect specific intracellular junction proteins to initiate and activate signaling pathways such as NF-κB to control the transcription of genes encoding IFN-I and other inflammatory cytokines to inhibit virus replication ( 28 ). A previous study found that human PLAU could activate the NF-κB signaling pathway and participate in the development of bile duct cancer ( 20 ). We found high homology between human and goat PLAU using sequence alignment and investigated whether goat PLAU was involved in RLR-mediated signaling.…”
Section: Resultsmentioning
confidence: 99%
“…In the IFN system, this function is mainly mediated by IFN-I. Human PLAU has been shown to activate inflammatory responses in the NF-κB pathway in previous studies, while RIG-I or MDA5 signaling pathways have been shown to induce NF-κB or IRF3-mediated IFN-I production after viral stimulation, and IFN-I activates the JAK-STAT signaling pathway ( 20 , 37 , 38 ). Therefore, we suspected that goat PLAU influenced PPRV replication by promoting IFN-I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLAU has been documented to interact with GLIPR1 to activate EGFR signaling, consequently preventing from cigarette smoke-induced inflammatory response and airway damage [ 19 ]. PLAU shows the ability to activate NF-κB signaling to drive the development of cholangiocarcinoma [ 20 ]. PLAU is upregulated in lung cancer and can promote lung cancer cell invasion [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%